Extraction and characterization of lignin from oil palm biomass via ionic liquid dissolution and non-toxic aluminium potassium sulfate dodecahydrate precipitation processes - Mohtar, S.S. (Elsevier Ltd, 2015)
The objective of this study is to extract and characterize lignin from oil palm biomass (OPB) by dissolution in 1-butyl-3-methylimidazolium chloride (bmimCl), followed by the lignin extraction through the CO2 gas purging prior to addition of aluminum potassium sulfate dodecahydrate (AlK(SO4)2·12H2O). The lignin yield, YL (%wt.) was found to be dependent of the types of OPB observed for all precipitation methods used. The lignin recovery, RL (%wt.) obtained from CO2-AlK(SO4)2·12H2O precipitation was, however dependent on the types of OPB, which contradicted to that of the acidified H2SO4 and HCl solutions of pH 0.7 and 2 precipitations. Only about 54% of lignin was recovered from the OPB. The FTIR results indicate that the monodispersed lignin was successfully extracted from the OPT, OPF and OPEFB having a molecular weight (MW) of 1331, 1263 and 1473g/mol, and degradation temperature of 215, 207.5 and 272°C, respectively. © 2015 Elsevier Ltd.